2020
DOI: 10.3390/pathogens9020117
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Bioremediation and PGP Traits in Streptomyces as Strategies for Bio-Reclamation of Salt-Affected Soils for Agriculture

Abstract: Environmental limitations influence food production and distribution, adding up to global problems like world hunger. Conditions caused by climate change require global efforts to be improved, but others like soil degradation demand local management. For many years, saline soils were not a problem; indeed, natural salinity shaped different biomes around the world. However, overall saline soils present adverse conditions for plant growth, which then translate into limitations for agriculture. Shortage on the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 194 publications
(253 reference statements)
0
15
0
Order By: Relevance
“…Among the season-associated Bacteria, WMSS identified the nitrogen-fixing Bradyrhizobium genus [ 77 ], already reported in olive by [ 41 ], the anaerobes Peptoniphilus [ 78 ], which include human pathogenic species, and the Streptomyces genus, whose members are known as bioremediators and plant-growth-promoters [ 79 ]. The only WMSS and 16S/ITS rRNA gene shared genus was Malassezia that was positively associated to plants with high Xylella abundance.…”
Section: Discussionmentioning
confidence: 99%
“…Among the season-associated Bacteria, WMSS identified the nitrogen-fixing Bradyrhizobium genus [ 77 ], already reported in olive by [ 41 ], the anaerobes Peptoniphilus [ 78 ], which include human pathogenic species, and the Streptomyces genus, whose members are known as bioremediators and plant-growth-promoters [ 79 ]. The only WMSS and 16S/ITS rRNA gene shared genus was Malassezia that was positively associated to plants with high Xylella abundance.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Streptomyces strains have been utilized as PGPR for several crops, including wheat (Akbari et al, 2020 ), tomato (Hu et al, 2020 ), chickpea (Gopalakrishnan et al, 2015 ), sorghum (Gopalakrishnan et al, 2013 ), and rice (Suárez-Moreno et al, 2019 ). The PGP effects of these Streptomyces strains have been attributed to their production of siderophores and indole-3-acetic acid, nitrogen fixation, and phosphate solubilization, which make them potential biofertilizers (Romano-Armada et al, 2020 ). In addition, some of the Streptomyces strains could improve plant growth and production by increasing the plant resistance to phytopathogens and to the abiotic stresses, which is related to their production of chitinolytic enzymes (inhibiting insects and fungi), induction of non-specific plant resistance, production of bioactive compounds (VOCs), and antibiotic/siderophore production (Romano-Armada et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The PGP effects of these Streptomyces strains have been attributed to their production of siderophores and indole-3-acetic acid, nitrogen fixation, and phosphate solubilization, which make them potential biofertilizers (Romano-Armada et al, 2020 ). In addition, some of the Streptomyces strains could improve plant growth and production by increasing the plant resistance to phytopathogens and to the abiotic stresses, which is related to their production of chitinolytic enzymes (inhibiting insects and fungi), induction of non-specific plant resistance, production of bioactive compounds (VOCs), and antibiotic/siderophore production (Romano-Armada et al, 2020 ). From Streptomyces species, more than 120 volatile substances belonging to alkenes, esters, alcohols, and ketones have been detected (Schöller et al, 2002 ), and various functions of these VOCs have been reported in agriculture, including PGP effects and phytopathogen control (Olanrewaju and Babalola, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many physical, chemical, and biological strategies to address the problems of soil degradation contain the threat of salinity, such as salts leaching, chemical amelioration, organic amendments application, and planting of salt-tolerant species or varieties (Shankar and Evelin, 2019). Another biological approach to reclamation of salt-affected soils and recovery of their productivity is the use of biofertilizers based on halotolerant or halophile bacteria with plant growth-promoting (PGP) properties (Srivastava et al, 2019;Romano-Armada et al, 2020).…”
Section: Introductionmentioning
confidence: 99%